Evaluation of Disseminated Intravascular Coagulation in Critically Ill Pediatric Hemato-oncology Patients with Septic Shock - Jhang, Won Kyoung; Park, Seong Jong (Thrombosis and Haemostasis, 2020)
Background Disseminated intravascular coagulation (DIC) is a serious complication in septic shock. This study aimed to evaluate DIC and associated clinical outcomes using the International Society on Thrombosis and Hemostasis (ISTH) and modified ISTH overt DIC scores in critically ill pediatric hemato-oncology patients with septic shock.Methods Pediatric hemato-oncology patients with septic shock admitted to the pediatric intensive care unit (PICU) of a tertiary children's hospital between January 2013 and February 2020 were included. We modified the ISTH overt DIC score by eliminating the platelet domain and compared the performances of the ISTH and the modified ISTH overt DIC scores in DIC diagnosis and PICU mortality prediction of these patients.Results DIC was diagnosed in 56.4 and 38.5% of patients by ISTH and modified ISTH overt DIC scores, respectively. Patients with DIC showed a higher pediatric risk of mortality (PRISM) III, pediatric sequential organ failure assessment (pSOFA) scores, and PICU mortality than those without DIC (p < 0.05). The modified ISTH overt DIC score was an independent prognostic factor for PICU mortality and showed a larger area under the receiver operating characteristic curve than the ISTH overt DIC score (0.687 vs. 0.695). Addition of the DIC diagnosis improved the performance of PRISM III in predicting PICU mortality.Conclusion Critically ill pediatric hemato-oncology patients with septic shock frequently experience DIC, which was adequately evaluated by both ISTH and modified ISTH overt DIC scores. Considering the characteristics of these patients, the modified ISTH overt DIC score may be a promising prognostic factor for clinical outcomes in these critically ill pediatric patients.
Keywords: pediatric; disseminated intravascular coagulation; septic shock; intensive care unit